Are Australian Universities Engaging with their Annual Freedom of Speech and Academic Freedom Attestation Statements so as to Achieve their Intended Purposes? - Levine, Pnina (2024)
Freedom of speech and academic freedom have received considerable recent attention. The most significant development in Australia has arguably been the release in 2019 of former Chief Justice of the High Court of Australia, Robert French AC’s report containing a Model Code for the Protection of Free Speech and Academic Freedom (‘Model Code’). In 2021, former Deakin University Vice-Chancellor Professor Sally Walker undertook a review into the extent to which Australian universities had adopted the Model Code. One of her resulting recommendations was that each university’s governing body prepare an annual freedom of speech and academic freedom attestation statement to be published in the university’s annual reports. Walker’s primary purpose behind this requirement was to ensure compliance by universities with Australian higher education legislation requiring them to foster a university culture supportive of freedom of speech and academic freedom. This article considers the extent to which universities engaged with these attestation statements in their 2021 annual reports. It demonstrates that most universities are not completing attestation statements in a way that achieves their intended objectives. It highlights the risks to universities associated with this omission and provides guidance as to how attestation statements should be completed to reduce these risks.